2020
DOI: 10.3390/brainsci10080496
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia Profile in Relation to Negative Affect in Parents of Autistic and Typically Developing Young Children

Abstract: In our study, we explored the construct of alexithymia in parents of children with and without ASD using a multi-method approach based on self-rated and external rater assessment. We also assessed the level of self-report measures of negative affect states such as trait anxiety and depression, and investigated the correlation between the alexithymia construct, trait anxiety, and depression within the broader autism phenotype (BAP). A total sample of 100 parents (25 mothers and 25 fathers in each group) were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…A recent meta-analysis of published studies identi ed large differences between autistic adolescents/adults and neurotypical controls on self-reported alexithymia as measured by the Toronto Alexithymia Scale (TAS (2,33,34)), with an estimated 49.93% of autistic individuals exceeding cutoffs for "high alexithymia" on the twenty-item TAS (TAS-20), compared to only 4.89% of controls (3). Alexithymia has also been suggested to be part of the "Broader Autism Phenotype" (35)(36)(37), the cluster of personality characteristics observed in parents of autistic children and other individuals with high-levels of subclinical autistic traits (38). Along with verbal IQ, self-reported alexithymia is one of the stronger predictors of task-based emotion processing ability in the autistic population (29), and a number of studies measuring both alexithymia and core autism symptoms have concluded that alexithymia accounts for some or all of the emotion-processing differences associated with the categorical diagnosis of autism, such as impaired facial emotion recognition and differences in empathetic responses (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of published studies identi ed large differences between autistic adolescents/adults and neurotypical controls on self-reported alexithymia as measured by the Toronto Alexithymia Scale (TAS (2,33,34)), with an estimated 49.93% of autistic individuals exceeding cutoffs for "high alexithymia" on the twenty-item TAS (TAS-20), compared to only 4.89% of controls (3). Alexithymia has also been suggested to be part of the "Broader Autism Phenotype" (35)(36)(37), the cluster of personality characteristics observed in parents of autistic children and other individuals with high-levels of subclinical autistic traits (38). Along with verbal IQ, self-reported alexithymia is one of the stronger predictors of task-based emotion processing ability in the autistic population (29), and a number of studies measuring both alexithymia and core autism symptoms have concluded that alexithymia accounts for some or all of the emotion-processing differences associated with the categorical diagnosis of autism, such as impaired facial emotion recognition and differences in empathetic responses (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of published studies identified large differences between autistic adolescents/adults and neurotypical controls on self-reported alexithymia as measured by the Toronto Alexithymia Scale (TAS [2,33,34]), with an estimated 49.93% of autistic individuals exceeding cutoffs for "high alexithymia" on the twenty-item TAS (TAS-20), compared to only 4.89% of controls [3]. Alexithymia has also been suggested to be part of the "Broader Autism Phenotype" [35][36][37], the cluster of personality characteristics observed in parents of autistic children and other individuals with high-levels of subclinical autistic traits [38]. Along with verbal IQ, self-reported alexithymia is one of the stronger predictors of task-based emotion processing ability in the autistic population [29], and a number of studies measuring both alexithymia and core autism symptoms have concluded that alexithymia accounts for some or all of the emotion-processing differences associated with the categorical diagnosis of autism, such as impaired facial emotion recognition and differences in empathetic responses [39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of published studies identi ed large differences between autistic adolescents/adults and neurotypical controls on self-reported alexithymia as measured by the Toronto Alexithymia Scale (TAS (2,33,34)), with an estimated 49.93% of autistic individuals exceeding cutoffs for "high alexithymia" on the twenty-item TAS (TAS-20), compared to only 4.89% of controls (3). Alexithymia has also been suggested to be part of the "Broader Autism Phenotype" (35)(36)(37), the cluster of personality characteristics observed in parents of autistic children and other individuals with high-levels of subclinical autistic traits (38). Along with verbal IQ, self-reported alexithymia is one of the stronger predictors of task-based emotion processing ability in the autistic population (29), and a number of studies measuring both alexithymia and core autism symptoms have concluded that alexithymia accounts for some or all of the emotion-processing differences attributed to the categorical diagnosis of autism (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51).…”
Section: Introductionmentioning
confidence: 99%